"I Don't Know the Words He Uses": Therapeutic Communication among Q'eqchi Maya Healers and Their Patients. (25th March 2015) - Waldram, James B.
<x xml:space="preserve">Abstract</x> Traditional or indigenous healing is often assumed to involve rich forms of dialogical and symbolic communication between healer and patient that serve to explain its salience and efficacy. An ethnographic study of Q'eqchi Maya healing in Belize suggests, however, that communication in some forms of indigenous healing may also be minimal and peripheral to treatment and more akin to that of biomedicine than so‐called traditional medicine. While communication may still involve symbolic, intercorporeal, and other forms of subtle intersubjective connection, anthropologists often overreach in an effort to portray such healing systems in contradistinction to biomedicine. It is argued here that Q'eqchi healing might best be thought of as a form of empirically based restorative medicine in which communication is purely instrumental to the healer's task of diagnosing and eliminating pathology and restoring the health of the patient.